Effect of Cu addition on high-temperature oxidation behavior of 25Cr-20Ni austenitic stainless steel - Lee, Gunjick; Jung, Heechan; Ko, Yoon Seok; Kim, Dong-Ik; Sohn, Seok Su; Shim, Jae-Hyeok (Elsevier Editora Ltda, 2025)
The effect of Cu addition on the air oxidation behavior of 25Cr-20Ni austenitic stainless steels was investigated at 700 degrees C. The steel with Cu exhibited larger weight gain and greater oxide layer thickness than the steel without Cu. The transmission Kikuchi diffraction analysis results clearly indicated that the surface oxide scales consist of three distinct oxide phase layers in both steels. The overall oxide layer sequence was consistent with thermodynamic calculations; outermost Fe-rich corundum oxide, intermediate spinel oxide and inner Cr-rich corundum oxide layers. It seems that the presence of Cu increases the outward diffusion rate of alloying elements in both matrix and oxide layers during oxidation, eventually enhancing oxidation kinetics.